Exatidão de um novo dispositivo para escaneamento intraoral na captura da angulação e distância entre os implantes em arcos desdentados mandibulares - Pereira, Ana Larisse Carneiro (2020)
This non-randomized controlled cross-sectional study aims to analyze the accuracy of a new device for intraoral scanning in capturing the angle and distance of the implants in edentulous mandibular arches. 10 patients rehabilitated with fixed implant-supported total mandibular provisional prosthesis retained by four implants underwent three impression methods, SC group (intraoral scanning with digital bodies), SD group (intraoral scanning with the device) and CT group (transfer of implant position transfer). A laboratory scanner was used to digitize the physical models (group CT). From an inspection software (Gom Inspect), the STL files were superimposed to measure the three-dimensional coordinate system. Variations in coordinates for linear displacements (∆x, ∆ye ∆z), total 3D displacement (√∆ 2 + ∆ 2 + ∆ 2 ) and projection angles (∆θXY, ∆θXZ and ∆θYZ) were analyzed statistically (p=0,05). Then, the distances between the implants were measured using the same software mentioned. In the search for correlations between the coordinates and the distances between the implants, Spearman's correlation coefficient (p<0,05) was used. As for accuracy, the linear displacements for the SD group were higher than the SC group, for ∆y (Ⴟ SC: 2,82; Ⴟ SD: 0,63) and ∆z (Ⴟ SC: 2,06; Ⴟ SD: 0,70) (P <.05). No significant differences were found for ∆x (ႿSC: -0,17; ႿSD: -0,21) (p>0,05). As for angular displacements, SD showed less angular variation in the three projection planes compared to the SC group. The SD group showed accuracy to capture the distances between the implants (SC: 20,15; SD: 21,46; CT: 21,52) (p<0,05). There were no correlations between coordinates and distances. The new device for intraoral scanning (Group SD) showed accuracy for linear, angular displacements and distances between implants in mandibular edentulous arches.